Mobile phone and adolescents- addiction a mindful check in! - Sumesh Kumar, Sudhen (International Journal of Advanced Nursing Studies, 2014)
Mobile phones, one of the greatest inventions in the late 20th century, now have become the newest addiction in the world. Even though it has given us convenient and comfort, it doesn’t mean it has no adverse effect. It is something that is going to affect everyone on day to day basis. The concept and ideas of the adolescents with mobile phone use and mental health generated a possible pathway for personnel dependency and also for the direct sources of stress, depression, sleep disturbances, aggression, and to a list of risky behaviors. However, studies on the association between problematic mobile phone use and psychological problems have been relatively few until now. The impact of mobile phone in adolescents in different domains of mental health should be considered for epidemiological and interventional studies. Keywords: Adolescents, Cell Phone Use [CPU], Mobile Phone, Mobile Phone Use [MPU], Psychological Problems.